(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
This paper reviews key aspects of Nigeria’s fiscal and monetary policies with the aim of examining the performance of the policies. The paper provides a synthesis of key facts and draws policy conclusions which include the following: (i) fiscal policies such as the oil-price-based fiscal rule introduced in 2004 have increased fiscal discipline and reduced fiscal deficit in Nigeria, hence the policies should be maintained; and (ii) compared to the period of direct or controlled monetary policy approach, monetary policy has performed better in Nigeria under the market-based approach introduced in 1993, therefore the latter approach should be maintained.